Optimization of Polyvinyl Alcohol (PVA) and Glycerin in Kolang Kaling Peel-Off Gel Mask Formula (Arenga pinnata.) - Ni Putu Diah Swari Maharani; Intan Martha Cahyani; Eka Susanti Hanhadyanaputri (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2022)
Aging is caused by free radicals, one of which is ultraviolet light which can form ROS. Galactomannan compounds have the potential as antioxidants that can counteract free radicals. Kolang kaling contains many galactomannan compounds. Kolang kaling is processed into a peel-off gel mask, where PVA and glycerin are essential ingredients. PVA can form a polymer film layer, but if the layer is not balanced, glycerin is used as a humectant. The results of the FTIR analysis showed that the functional groups were D-galactopyranose and D-mannopyranose, which were characteristic of the functional groups of galactomannan. The IC50 of kolang kaling powder is 23.8720 ppm, a powerful antioxidant. The interaction of PVA and glycerin increased drying time, viscosity, antioxidant activity, and decreased dispersion, adhesion, and pH. The optimal formula obtained was 14.47% PVA and 15.73% glycerin. The results of the One Sample T-Test validity test found that the results of the equations of each test were valid.